Histopathological Effects of Potassium Bromate on Liver Male Rat's and Possible Protective Role of Ruta chalepensis L. (Rutacae) Oil Extract - Gheth, Ebtesam M. M.; Eldurssi, Ibrahim S; Algassi, Abdullah A. H.; Abdalla, Gasem M. A.; Hamad, Mabroka A. S. (Asian Journal of Pharmaceutical Research and Development, 2019)
Potassium bromate (KBrO3) is an oxidizing agent that has been used as a food additive, mainly in the bread-making process. Ruta chalepensis L. (Family-Rutaceae) is a small shrub, native to the Mediterranean Basin. The present study aimed to investigate the protective and curative effects of R. chalepensis oil extract against KBrO3 toxicity on liver of male rats. Fifty male albino rats were divided into five groups. The first group served as a control group. The second group was administered Rue at an oral daily dose of 0.5 g/Animal for four weeks. The third group received KBrO3 100 mg/kg/b. w. for four weeks. The fourth group (protective group) was initially administered Rue alone for 2 weeks and followed by KBrO3 in association with Rue for 2 weeks. The fifth group (therapeutic group) was first given KBrO3 alone for 2 weeks and was then administered Rue in association with KBrO3 for 2 weeks. At the end of 2nd and 4th weeks of treatment, the liver tissues were dissected out for histopathological studies. Histopathological sections of rats administered with Rue showed the same histological observations as in the liver of control animals. KBrO3 treated rats exhibited marked congestion and dilatation of the blood vessels, the central veins and the portal veins. Additionally, marked infiltrative inflammatory cells were revealed. The occurrence of the cellular necrobiotic lesions and nuclei in these necrotic cells showed pyknosis. They also, showed cellular atrophied and hyaline degeneration of the cytoplasm. Vacuoles of different shapes and sizes were developed in the hepatocytes. Blood vessels being thick walled and fibrotic encircled by an inflammatory area rich in leucocytes. The protective and therapeutic groups showed marked hepatoprotective activity and better improvement than that noticed in the group which was given KBrO3 only. It may be concluded from the results that the hepatotoxic effect of KBrO3 and the ameliorative effect of Rue an effective when administrated as protective and therapeutic measures. Keywords: Rat, Liver, Potassium Bromate, Ruta chalepensis, Histopathology.